Intra Cervical Foley’s Versus Combination Of Intra Cervical Foley’s And Extra Amniotic Saline Infusion As Cervical Ripening Agent For Induction Of Labor - Javed, Humera; Noreen, Humera; Bilqis, Humaira; Kahloon, Lubna Ejaz; Khalid, Iqra; Bano, Naheed (Journal of Rawalpindi Medical College, 2024)
Objective: To compare IntraCervical Foleys (ICF) and intracervical Foleys along with Extra Amniotic Saline Infusion (EASI) as a cervical ripening agent for Induction Of Labour(IOL). Methods: It was carried out at the Department of Obstetrics and Gynecology Holy Family Hospital, Rawalpindi. In this comparative study, we included 100 patients with singleton cephalic presentation, intact membranes and a BISHOP score ≤ 6. These were further subdivided into two groups, Group A (ICF) and Group B (ICF with EASI),50 in each group. In Group A, Foley’s catheter was placed cervically while in Group B extraamniotic saline infusion was also administered in the urine drainage port at midnight. PGE2/ Augmentation with syntocinon was considered according to the bishop score at 6 am. Improvement in BISHOP score, induction to delivery interval, and feto-maternal outcomes were noted in both groups. Results: Data analysis showed that the mean improvement in the BISHOP score of the patients in Group A was 3.78 ± 1.75 while that of Group B was 3.56 ± 1.79(pvalue = 0.508). The induction to delivery interval in group A patients was 14.6 ± 4.75 hours while that of group B was 13.22 ± 4.54 hours (p =0.103). Only 14/100 patients had failed IOL and underwent C- C-sections and 8/100 neonates had NICU admissions and were discharged later on. Conclusion: Both Intra Cervical Foley’s and a Combination Of Intra Cervical Foley’s And Extra Amniotic Saline Infusion are equally effective as cervical ripening agents for induction Of labour with high chances of successful vaginal delivery and good feto-maternal outcome. Keywords: Induction of labour, Intracervical folleys, Extra-amniotic saline infusion, BISHOP score.